Sodium Hyaluronate Supplemented Culture Media as a New hMSC Chondrogenic Differentiation Media-Model for in vitro/ex vivo Screening of Potential Cartilage Repair Therapies - Monaco, Graziana; El Haj, Alicia Jennifer; Alini, Mauro; Stoddart, Martin James (Frontiers in Bioengineering and Biotechnology, 2020)
Surgical strategies to treat articular cartilage injury such as microfracture, expose human bone marrow stem cells (hMSCs) to synovial fluid and its components. High molecular weight hyaluronan (hMwt HA) is one of the most abundant bioactive macromolecules of healthy synovial fluid (hSF) and it plays an important role in the protection of opposing articular cartilage surfaces within the synovial joint. Although hMwt HA has been extensively used to attempt the engineering of the cartilage tissue, its effect as media supplement has not been established. Indeed, current media are often simple in their composition and doesn't recapitulate the rheological and biological features of hSF. In addition, critical in vivo molecules that can potentially change the chondrogenic behaviour of hBMSCs to make the in vitro results more predictive of the real in vivo outcome, are lacking. In order to be one step closer to the in vivo physiology of hSF, a new culture media supplemented with physiological level of hMwt HA was developed and the effect of the hMwt HA on the chondrogenesis of hMSCs that would be present in a traumatic defect after marrow stimulation techniques, was investigated. hBMSC-seeded fibrin-polyurethane constructs were cultured in a serum free chondropermissive control medium (HA- TGFβ-). This medium was further supplemented with 10 ng/mL TGFβ1 (HA- TGFβ+) or 2mg/ml hMwt HA 1.8 MDa (HA+ TGFβ-) or both (HA+ TGFβ+). Alternatively, 1 MDa HA was mixed with the fibrin at 0.2mg/ml (HASc TGFβ+). The effect of hMwt HA on hMSC differentiation was investigated at the gene expression level by RT-qPCR and total DNA, sulphated glycosaminoglycans and Safranin O staining were evaluated. Addition of hMwt HA to the culture media, significantly increased the synthesis of sulphated glycosaminoglycans, especially in the early days of chondrogenesis, and reduced the upregulation of the hypertrophic cartilage marker collagen X. hMwt HA added inside the fibrin gel (HASc TGF+) led to the best matrix deposition. hMwt HA can be one key medium component in a more reliable in-vitro/ex-vivo system to reduce in-vitro artefacts, enable more accurate pre-screening of potential cartilage repair therapies and reduce the need for animal studies.